2016
DOI: 10.1186/s40623-016-0547-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface fault ruptures associated with the 14 April foreshock (Mj 6.5) of the 2016 Kumamoto earthquake sequence, southwest Japan

Abstract: The 2016 Kumamoto earthquake sequence was a rare event worldwide in that the surface ruptures associated with the largest foreshock (Mj 6.5) of 21:26 (JST), 14 April ruptured again during the mainshock (Mj 7.3) of 01:25 (JST), 16 April. The 14 April Mj 6.5 earthquake produced 6-km-long surface ruptures along the central portion of the Futagawa-Hinagu fault zone (FHFZ). The mainshock produced 31-km-long surface ruptures along the central to northeastern part of the FHFZ. Field observations and eyewitness accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…The features of earthquake-induced surface ruptures mainly include extensional fissures, local uplift, bulging, and subsidence [4][5][6]51]. In this experiment, there are two macroscopic fracturing modes: extensional fissures and local bulging.…”
Section: Fracturing Modementioning
confidence: 95%
See 1 more Smart Citation
“…The features of earthquake-induced surface ruptures mainly include extensional fissures, local uplift, bulging, and subsidence [4][5][6]51]. In this experiment, there are two macroscopic fracturing modes: extensional fissures and local bulging.…”
Section: Fracturing Modementioning
confidence: 95%
“…Rock failure can result in different types of surface fracturing modes, including extensional fissures, local bulging, and subsidence, along active faults [1][2][3]. Hence, basic information on crustal activity, including the deformation mode, motion state of a fault and the fracture process, can be reflected by the movement characteristics of surface rupture [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Both ruptures showed right-lateral strike slip displacements of about 50-100 cm with slight uplift of southern side. The surface ruptures were described by topographical field investigations (Shirahama et al, 2016;Sugito, et al, 2016) but also traced clearly from aerial photographs taken after the earthquakes. It is characteristic that both ruptures extend to divide a wedge-shaped lowland where Kiyama and Akitsu River flow through.…”
Section: Study Sitementioning
confidence: 99%
“…1a). Significant surface ruptures associated with the earthquake sequence appeared in Mashiki Town, which is located at the junction of the two major fault zones (Shirahama et al 2016;Sugito et al 2016;Toda et al 2016) and seismic intensity of 7, the maximum seismic intensity scale of the Japan Metrological Agency (JMA), was measured during both larger events. The results of damage investigations (e.g., National Institute for Land and Infrastructure Management and Building Research Institute 2016; Sugino et al 2016b;Tomozawa et al 2017;Yamada 2017;Yamada et al 2017a, b) showed that heavily damaged buildings were concentrated in a narrow region between Kumamoto Prefectural Route 28 (R28) and the Akitsu River running from east to west in the central part of Mashiki (Fig.…”
Section: Introductionmentioning
confidence: 99%